Sharing published short academic works in institutional repositories after six months: The implementation of the article 25fa (Taverne Amendment) in the Dutch Copyright Act - Sondervan, Jeroen; Schalken, Arjan; Jan de Boer,; Saskia Woutersen-Windhouwer, (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2021)
The ambition of the Netherlands, laid down in the National Plan Open Science, is to achieve 100% open access for academic publications. The ambition was to be achieved by 2020. However, it is to be expected that for the year 2020 between 70% and 75% of the articles will be open access. Until recently, the focus of the Netherlands has been on the gold route - open access via journals and publishers’ platforms. This is likely to be costly and it is also impossible to cover all articles and other publication types this way. Since 2015, Dutch Copyright Act has offered an alternative with the implementation of Article 25fa (also known as the ‘Taverne Amendment’), facilitating the green route, i.e. open access via (trusted) repositories. This amendment allows researchers to share short scientific works (e.g. articles and book chapters in edited collections), regardless of any restrictive guidelines from publishers. From February 2019 until August 2019 all Dutch universities participated in the pilot ‘You Share, we Take Care!’ to test how this copyright amendment could be interpreted and implemented by institutions as a policy instrument to enhance green open access and “self-archiving”. In 2020 steps were taken to scale up further implementation of the amendment. This article describes the outcomes of this pilot and shares best practices on implementation and awareness activities in the period following the pilot until early 2021, in which libraries have played an instrumental role in building trust and working on effective implementations on an institutional level. It concludes with some possible next steps for alignment, for example on a European level.